2015
DOI: 10.1007/s11692-015-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

Body Shape Evolution in Sunfishes: Divergent Paths to Accelerated Rates of Speciation in the Centrarchidae

Abstract: Vertebrate evolutionary radiations are the result of divergence along a variety of ecological and behavioural axes. In addition, the potential for clades to evolve along any one axis can be strongly influenced by the types and levels of phenotypic variation that are exposed to natural selection. Understanding the factors that promote and constrain morphological diversification is a central goal of evolutionary biology. Here we use the sunfishes (Centrarchidae), a perciform family containing three main clades (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
(77 reference statements)
0
14
1
Order By: Relevance
“…Our results differ from those found by previous HCHsupporting studies, which suggested that feeding at high trophic levels might constrain morphological evolution in fishes 17,19,51 , as well as non-fish taxa 52 . One reason could be the broad phylogenetic sampling of our dataset in contrast with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from those found by previous HCHsupporting studies, which suggested that feeding at high trophic levels might constrain morphological evolution in fishes 17,19,51 , as well as non-fish taxa 52 . One reason could be the broad phylogenetic sampling of our dataset in contrast with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies focused on single species or small clades suggest that the evolution of high trophic position should constrain rates of functional trait evolution due to the constraints imposed by feeding on evasive energy-rich prey items relative to lower trophic levels [16][17][18][19] . We term this the height constraint hypothesis (HCH).…”
mentioning
confidence: 99%
“…other fishes, shrimps) typically have large mouths and utilize fast ram strikes (Higham, 2007;Higham et al, 2007), but large mouths reduce suction feeding ability, which is only efficient within roughly one mouth diameter from the prey (Day et al, 2005;Wainwright et al, 2001). Although planktivorous damselfishes do have the largest standardized gapes (Table 5), their mouth sizes are nowhere near as large as those of piscivorous groupers (Serranidae), sunfishes (Centrarchidae) or cichlids (Cichlidae), and remain small enough to promote suction production (Cooper et al, 2010;Oufiero et al, 2012;Smith et al, 2015). We see no body ram specialists among the damselfishes and it has recently been suggested that the structure of their pharyngeal jaws may constrain their ability to specialize in larger prey, such as elusive fishes, whose capture is facilitated by body ram feeding strikes (McGee et al, 2015a).…”
Section: Trade-offs In Damselfish Feedingmentioning
confidence: 99%
“…Not only do sunfish have different feeding kinematics but, compared with the fusiform bass, they also have shorter, deeper and more laterally compressed bodies and a smaller gape (Fig. 1B) (Smith et al, 2015;Werner, 1977).…”
Section: Introductionmentioning
confidence: 99%